Synthesis, Characterization and Sensing Mechanism of a Novel Fluorescence Probe for Fe(III) in Semi-Aqueous Solution Based on a Schiff Base Hexadentate Receptor - Ooshall, Farkhondeh; Jamehbozorgi, Saeed; Golbedaghi, Reza; Justino, Licinia L. G.; Feshalame, Keyvan Mirzaei; Liyaghati-Delshad, Mozhdeh; Anaraki-Ardakani, Hossein; Jaleh, Babak; FAUSTO, RUI (Elsevier Science SA, 2023)
A new acyclic Schiff base chemosensor L was synthesized by the one pot condensation reaction of 2-[3-(formyl phenoxy)2-hydroxypropoxy]benzaldehyde and 2-aminophenol in a 1:2 molar ratio and was characterized by elemental analysis, FTIR, 1H- and 13C NMR, and fluorescence spectroscopies. These studies were complemented with a thorough conformational study at the molecular mechanics and density functional theory (DFT) levels of theory to further elucidate the structure of the compound in solution. The chemosensor L displays high sensitivity and selectivity for Fe3+ in semi-aqueous (H2O-DMF, 1:1) solution, except in the presence of a significant amount of Ni2+, with the presence of Fe3+ being signaled through the total fluorescence quenching of the fluorophore when Fe3+ binds to the recognition unit. The synthesized ligand also shows high selectivity for Fe3+ compared to the metal ions Cu2+, Zn2+, Mg2+, Mn2+, Pb2+, Hg2+, Na+, Ba2+ and Cd2+, and reasonable selectivity in the presence of Ag+, Co2+ and Cr3+. The stoichiometry and structure of the complex formed between Fe3+ and the probe L were determined from a Job's plot and DFT calculations, respectively. The complex was characterized as a high-spin 1:1 octahedral species, in which the ligand coordinates to the metal through the two ether oxygen atoms, two nitrogen atoms and two terminal hydroxyl groups. Time dependent (TD-DFT) calculations were performed to provide information on the type of mechanism causing the quenching of the fluorescence in the presence of Fe3+.
Keywords: Fluorescence Sensor; Fe3+; Aminophenol; Schiff Base; Sensitive; DFT Calculations